2019
DOI: 10.3390/agronomy9120780
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Green Manure Rotations Improve Soil Biochemical Properties, Yield Sustainability and Nutrient Balances in Acidic Paddy Soil under a Rice-Based Cropping System

Abstract: Cultivation of green manure (GM) crops in intensive cropping systems is important for enhancing crop productivity through soil quality improvement. We investigated yield sustainability, nutrient stocks, nutrient balances and enzyme activities affected by different long-term (1982–2016) green manure rotations in acidic paddy soil in a double-rice cropping system. We selected four treatments from a long-term experiment, including (1) rice-rice-winter fallow as a control treatment (R-R-F), (2) rice-rice-milkvetch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 63 publications
3
6
0
1
Order By: Relevance
“…These results could be due to the manure addition, which supplies enough nutrients to the soil, primarily by directly increasing carbon inputs into the soil, which assists in carbon sequestration. Similar results were reported in previous long-term studies [ 39 , 40 ]. Long-term NPK plus manure addition significantly increased the soil total P and available P concentrations in the soil at all three sites ( Table 3 ).…”
Section: Resultssupporting
confidence: 92%
“…These results could be due to the manure addition, which supplies enough nutrients to the soil, primarily by directly increasing carbon inputs into the soil, which assists in carbon sequestration. Similar results were reported in previous long-term studies [ 39 , 40 ]. Long-term NPK plus manure addition significantly increased the soil total P and available P concentrations in the soil at all three sites ( Table 3 ).…”
Section: Resultssupporting
confidence: 92%
“…The article by Qaswar et al [29] summarizes a long-term study on green manure rotations on an acidic paddy soil in a double rice (Oriza sativa L.) cropping system. Compared to a rice-rice-winter fallow cropping system, replacing winter fallow with a green manure crop improved grain yield and the sustainable yield index of early and late rice, soil organic matter, soil total and available N and phosphorus, and phosphatase and urease activities, and reduced the apparent N and phosphorus balances.…”
Section: Crop Rotationmentioning
confidence: 99%
“…Long-term experiments offer important advantages relative to short-term studies in providing valuable information on the effect of fertilization management on the sustainability of crop production (Manna et al, 2005;Qaswar et al, 2019;Han et al, 2020). Studies have reported that the sustainable yield index (SYI) of rice and wheat has a positive relationship with SOC content (Wanjari et al, 2004;Qaswar et al, 2019). These findings suggest that SOC plays an important role in improving crop yield stability under climate change (Manna et al, 2005;Han et al, 2020;Shi et al, 2022).…”
Section: Introductionmentioning
confidence: 99%